Kinetic study on mercury HG (II) removal by CNT - Kabbashi, Nassereldeen Ahmed; Mirghani, Mohamed Elwathig Saeed; AbuSam, Abdallah; Jamil, Illi Nadirah (World Academic Publishing, 2015)

(untitled)
Kinetic of modeling data is necessary for the industrial use of adsorption. Under changed conditions, kinetic offers evidence for operational conditions for designing and optimizing effective situations for removing the pollutant. The pseudo second-order equation was used in this study in order to investigate the mechanism of adsorption of mercury by the CNTs and the potential rate-controlling steps, such as mass transport and chemical reactions. The interaction model shows how contact with different pH affects the residual concentration of the mercury at two different times. The first (contact time of 20 minutes) showcase of the removal of the mercury does not reduce much when the pH varies from pH 5 to pH 8. The second (contact time of 120 minutes) however shows that the pH affects the removal of mercury at pH 5, the residual concentration was lower compared to the residual concentration at pH 8.